(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Facing reduction in public funding and increases in pressure to improve student performance and graduation rates, many public colleges and some state systems have implemented flat rate tuition policies. This study looks at the relationship between such a policy and undergraduate student performance (changes in GPA) and persistence (credits attempted vs. earned) at one public college during four consecutive academic terms. The study reveals a strong correlation between student persistence and performance. Students who persist in completing heavier credit loads are more likely to experience small and diminishing GPA gains; and students who do not persist are more likely to experience GPA losses of significantly lower magnitude. Students who attempt lower course loads are more likely to persist than those who attempt heavier course loads. These correlations are statistically significant so that they may be extrapolated to the whole student population in the college.